Probing type Ia supernova properties using bolometric light curves from the Carnegie Supernova Project and the CfA Supernova Group. Issue 1 (29th November 2018) - Scalzo, R A; Parent, E; Burns, C; Childress, M; Tucker, B E; Brown, P J; Contreras, C; Hsiao, E; Krisciunas, K; Morrell, N; Phillips, M M; Piro, A L; et al.
ABSTRACT: We present bolometric light curves constructed from multiwavelength photometry of Type Ia supernovae (SNe Ia) from the Carnegie Supernova Project and the CfA Supernova Group, using near-infrared observations to provide robust constraints on host galaxy dust extinction. This set of light curves form a well-measured reference set for comparison with theoretical models. Ejected mass and synthesized 56 Ni mass are inferred for each SN Ia from its bolometric light curve using a semi-analytic Bayesian light curve model, and fitting formulas provided in terms of light curve width parameters from the salt2 and SNooPy light curve fitters. A weak bolometric width–luminosity relation is confirmed, along with a correlation between ejected mass and the bolometric light curve width. SNe Ia likely to have sub-Chandrasekhar ejected masses belong preferentially to the broad-line and cool-photosphere spectroscopic subtypes, and have higher photospheric velocities and populate older, higher mass host galaxies than SNe Ia consistent with Chandrasekhar-mass explosions. Two peculiar events, SN 2006bt and SN 2006ot, have normal peak luminosities but appear to have super-Chandrasekhar ejected masses.